Evaluation on the factors which contribute to the level of job satisfaction among Medical Officers at Hospital Tuanku Ampuan Najihah (HTAN) / Nadiah Abdul Latif - Abdul Latif, Nadiah (Faculty of Business and Management, 2013)
There are declining and low level of job satisfaction among Medical Officer at HTAN. Dissatisfaction among Medical Officers has cause the reduction in the quality of care. Low level of job satisfaction and high level of job stress are threats to mental and physical health, quality of life goal achievement, and personal development among the Medical Officers. At the work place, these conditions can lead to absenteeism, accidents, conflict and turnover, and reduced quality and quantity of work. Low level of job satisfaction become a problem for the retention of existing doctors because there some of Medical Officers that quit from their job due to burnout and low level of job satisfaction. The issue of job satisfaction is very important because recently there are lots of grouses and dissatisfactions amongst the medical officers regarding the promotion, rewards, long working hours, workloads, work pressure, work environment apart from the public complaints on the government poor medical service. The objective of this study is to examine the most important aspect for each factor hospital management factor, hospital facilities and equipment factor and healthcare providers factor that lead to job satisfaction among Medical Officers at HTAN and to identify the most effective factor that lead to job satisfaction among Medical Officers at HTAN. The population of this study is focusing to all Medical Officers in all departments at HTAN. According to the sample size in the table ‘Sample Size for a Given Population Size’ provided by Krejcie and Morgan (1970). As the population for Medical Officers at HTAN is 129, sample size for this study must be 97. The sampling frame is all Medical Officers in all departments at HTAN. This study use probability sampling which is stratified random sampling. 97 respondents have been chose as sample. All the questions in the questionnaire are adopted and adapted from the journal Job Satisfaction Among Doctors And Nurses (A case study of Federal Medical Centre Yola) (2011). This study use personally administered questionnaire as data collecting method. The questionnaire consists of Likert Scale Questions that are designed to examine how strongly subject’s satisfied or dissatisfied with statements on a five-point scale. This study was done to see the significant correlation between hospital management factor, hospital facilities and equipment factor and healthcare providers factor, with the level of job satisfaction among medical officers at HTAN. According to the findings, the entire variable seems to have a significant correlation. Therefore all the factors are supported in this study.